2024
DOI: 10.1029/2023gl106662
|View full text |Cite
|
Sign up to set email alerts
|

Link Between Geometrical and Physical Property Changes Along Nankai Trough With Slow Earthquake Activity Revealed by Dense Reflection Survey

Paul Caesar M. Flores,
Shuichi Kodaira,
Gaku Kimura
et al.

Abstract: We examined the possible factors affecting the spatial distribution of very low frequency earthquakes and tremors in the shallow megathrust of Nankai Trough (<30 km) using a dense network of prestack depth migrated profiles at the frontal wedge. Geometrical parameters examined were decollement roughness, taper angle, and underthrust thickness. Physical properties such as effective basal friction (μb) and pore pressure ratio (λ*) were calculated from the taper angle and p‐wave velocity. Regions of low λ* (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…Underthrusting of rather small scale seamount (H/L = ∼1.5 km/∼10 km) is also reported at off-Muroto to the south of the Tosabae seamount (Bangs et al, 2006;Nakamura et al, 2022;Park et al, 1999), which is included in the slow earthquake area. The basement highs reported in this paper to the southwest of the Paleo Zenisu Ridge have an H/L of ∼1/10 with length of ∼15 km (Figure 7) as well as those at the off-Muroto Nankai forearc, where Flores et al (2023) reported that the roughness of the plate boundary surface is larger than that of the surrounding area.…”
Section: Topographic and Structural Host For The Slow Earthquakessupporting
confidence: 48%
“…Underthrusting of rather small scale seamount (H/L = ∼1.5 km/∼10 km) is also reported at off-Muroto to the south of the Tosabae seamount (Bangs et al, 2006;Nakamura et al, 2022;Park et al, 1999), which is included in the slow earthquake area. The basement highs reported in this paper to the southwest of the Paleo Zenisu Ridge have an H/L of ∼1/10 with length of ∼15 km (Figure 7) as well as those at the off-Muroto Nankai forearc, where Flores et al (2023) reported that the roughness of the plate boundary surface is larger than that of the surrounding area.…”
Section: Topographic and Structural Host For The Slow Earthquakessupporting
confidence: 48%